Co-Ni based hybrid transition metal oxide nanostructures for cost-effective bi-functional electrocatalytic oxygen and hydrogen evolution reactions. (1st January 2020) - Mohan Kumar, G.; Ilanchezhiyan, P.; Siva, C.; Madhankumar, A.; Kang, T.W.; Kim, D.Y.
Abstract: Water splitting is widely regarded as one of the promising technologies for hydrogen fuel production and foreshadowed to assist in meeting the global energy demand as a sustainable and reliable energy technology. In this regard, we report on the facile chemical synthesis of hybrid Cobalt (Co) and Nickel (Ni) oxide nanostructure for low-cost bi-functional electrocatalytic water splitting applications. Their crystalline characteristics and chemical structure were studied using X-ray diffraction and Fourier-Transform infrared (FT-IR) spectrum. The nanostructure morphology was investigated by scanning and high-resolution transmission electron microscopy (SEM/HRTEM). The 2 + and 3 + valence state of Co and Ni metal ions was identified using X-ray photoelectron spectroscopy (XPS). The hybrid oxide electrocatalyst was found to display an excellent oxygen/hydrogen evolution reaction (OER/HER activity) in alkaline condition. The realization of random heterojunction configuration across the hybrid nanostructures was found to offer an improved conductivity and enhanced charge transfer capability to promote the gas evolution kinetics. Overpotential value of 203 and 378 mV was registered from the respective OER and HER polarization curves (for current density of ±10 mA cm −2 ). Tafel slope of 87 mV/dec for OER and 90 mV/dec for HER along with the long-term stability results authenticated the anodic/cathodic characteristics of hybrid oxides for overall water splitting applications. Graphical abstract: Image 1 Highlights: Co3 O4 -NiO hybrid structures were processed via one pot facile aqueous synthesis route. Hybrids exhibit excellent bifunctional electrocatalytic potential for water splitting. OER/HER Tafel slope of 87 and 90 mV/dec were recorded. High durability was confirmed by consistent reactivity of hybrid catalyst.